A PID-based automatic generation control simulator for the Terco PST 2200 - Co, Jarvin Cassidy B.
We developed an Automatic Generation Control (AGC) simulator for the UP PSSL Terco PST 2200 power system simulator. The AGC Simulator is implemented with a programmable logic controller (PLC) equipped with a PID control loop as the main controller, a PLC-based HMI operator panel, and a remote PC-based monitoring and control centre. It is capable of running a prime mover-generator setup in the following modes of operation: base load, automatic, manual and forecast. Designed for training electrical engineering students and power engineers in generation control, the ACG simulator allows users to specify the setpoints for controlling the generator voltage, frequency, and power output and the parameters of the PID control loop.